Brightness of blood: Review of fluorescence spectroscopy analysis of bloodstains - Weber, Alexis; Lednev, Igor K. (Frontiers in Analytical Science, 2022)
Luminescence spectroscopy is a versatile analytical technique that measures the emitted light resulted from the radiative deactivation of electronically excited states of molecular an atomic species. The field of forensic science has implemented the use of fluorescence spectroscopy for the analysis of bloodstains. Bloodstains discovered at crime scenes can provide crucial information to an investigation. It allows for the identification of the individual providing that there is a match with a known DNA profile. Additionally, determining the time since deposition (TSD) can assist investigators in establishing when the crime occurred or if a bloodstain present is related to the investigated event. However, most techniques that researchers have utilized thus far focus on the analysis of hemoglobin, both for identification and TSD determinations. Unlike other techniques, fluorescence spectroscopy can investigate the endogenous fluorophores within bloodstains. In this brief review, the ability of fluorescence spectroscopy for the analysis of bloodstains will be discussed. Including the ability to identify, determine the time since deposition, and phenotypic characterization of bloodstains.